IMPLEMENTASI NILAI-NILAI QUR’ANI DALAM KEPEMIMPINAN KEPALA SEKOLAH DAN PENGEMBANGAN PROFESIONALISME GURU DI SDIT - Lina Ari Setiyawati; Suhada Suhada; Hamam Faizin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Modern educational leadership in 2026 is often trapped by rigid bureaucracy, ignoring the moral-spiritual aspects of the Quran as a complete guide to life. The gap between formal power orientation and the integrity of the murabbi (leader) is a major problem hindering the substantial development of the teaching profession. This study aims to explore the synergy between managerial practices and prophetic values ​​at SDIT Rafflesia Depok through a mixed-methods sequential exploratory design. The research began with a qualitative phase through participant observation and in-depth interviews with thirty-seven participants, followed by quantitative measurement using a questionnaire instrument with proven reliability. The study findings revealed that the systematic internalization of the qualities of shiddiq (honest), amanah (trustworthy), fathonah (faithful), and tabligh (prophetic) can create policy transparency and a healthy organizational culture. The principal acts as a good example, empowering teachers through the use of smart technology and collective knowledge-sharing sessions. Quantitatively, the management of forty personnel and four hundred and eighty-three students resulted in a highly significant level of parental satisfaction. The main conclusion confirms that the integration of Quranic values ​​into school leadership is not merely a formality, but rather a key driver in building a competitive, holistic educational ecosystem. The prophetic leadership paradigm has proven effective in enhancing the pedagogical competence and moral fortitude of teaching staff amidst the dynamics of massive global change and challenges in today's digital era, enabling them to realize the profile of a noble civilization. ABSTRAK Kepemimpinan pendidikan modern tahun 2026 sering terjebak birokrasi kaku, mengabaikan aspek moral-spiritual Al-Qur'an sebagai pedoman hidup paripurna. Kesenjangan antara orientasi kekuasaan formal dan integritas murabbi menjadi masalah utama yang menghambat pengembangan profesi guru secara substansial. Penelitian ini bertujuan mengeksplorasi sinergi praktik manajerial dengan nilai-nilai kenabian di SDIT Rafflesia Depok melalui metode campuran desain sequential exploratory. Langkah penelitian diawali dengan fase kualitatif melalui observasi partisipatif serta wawancara mendalam terhadap tiga puluh tujuh partisipan, dilanjutkan dengan pengukuran variabel kuantitatif menggunakan instrumen angket yang teruji reliabilitasnya. Temuan studi mengungkapkan bahwa internalisasi sifat shiddiq, amanah, fathonah, dan tabligh secara sistematis mampu menciptakan transparansi kebijakan dan budaya organisasi yang sehat. Kepala sekolah bertindak sebagai uswah hasanah yang memberdayakan guru melalui pemanfaatan teknologi cerdas dan sesi berbagi pengetahuan kolektif. Secara kuantitatif, pengelolaan empat puluh personel terhadap empat ratus delapan puluh tiga siswa menghasilkan tingkat kepuasan orang tua yang sangat signifikan. Simpulan utama menegaskan bahwa integrasi nilai Qur'ani dalam kepemimpinan sekolah bukan sekadar formalitas, melainkan penggerak utama dalam membangun ekosistem pendidikan holistik yang kompetitif. Paradigma prophetic leadership terbukti efektif meningkatkan kompetensi pedagogik serta keteguhan moral staf pengajar di tengah dinamika perubahan global yang masif dan penuh tantangan di era digital saat ini guna mewujudkan profil peradaban luhur.